2015
DOI: 10.1039/c5ra09739h
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a silicon wafer texturing process by modifying the texturing temperature for heterojunction solar cell applications

Abstract: A simple and effective method using a two-step texturing temperature control is proposed to optimize the texturing process of commercial Cz-silicon wafers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
3
3
0
Order By: Relevance
“…However, the size of the pyramids is not homogeneous over the entire surface, as shown in Figure b,c and f. After 25 min, there are more larger pyramids while the largest size seems to be stable at about 20 μm on a side and the surface coverage further increases to nearly 100% after 45 min of reaction time (Figure d,e). With increasing reaction time, the pyramids become more regular and are more uniformly distributed on the Si surface, which is consistent with the previous literature . Importantly, as more and more pyramids are formed on the surface, the surface area increases with the etching duration.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, the size of the pyramids is not homogeneous over the entire surface, as shown in Figure b,c and f. After 25 min, there are more larger pyramids while the largest size seems to be stable at about 20 μm on a side and the surface coverage further increases to nearly 100% after 45 min of reaction time (Figure d,e). With increasing reaction time, the pyramids become more regular and are more uniformly distributed on the Si surface, which is consistent with the previous literature . Importantly, as more and more pyramids are formed on the surface, the surface area increases with the etching duration.…”
Section: Resultssupporting
confidence: 91%
“…The reflectance spectra of the silicon surface with different pyramid coverages are shown in Figure and Figure , Supporting Information. The overall reflectance of the silicon surface reduces with the coverage through the visible and near infrared range (from 300 to 1100 nm), which is consistent with previous observations . However, the reflectance of the Si surface with 99.9% coverage of pyramids is higher than in previous reports (18% vs 13% to be the lowest reflectance) .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the case of monocrystalline silicon, a random upright pyramid texture, created by wet alkaline etching, is most commonly used. [15][16][17][18] This texture reduces reflectance and increases light trapping, and thus contributes to an increase in the current output of the solar cell 15,[19][20][21] and is also cheaper to realize than a perfectly planar substrate surface. In this paper, it is shown that such substrates coloured with single layer thin film coatings possess better angular colour stability than planar substrates coated with identical coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Chemical polishing is an effective way to modify the pyramid profile. A common method of chemical polishing is etching textured wafer in an HNO 3 + HF solution, 6,[8][9][10][11] which has been applied on an industrial scale in Panasonic's HIT solar cell factories. 12,13 In recent years, ozone-based bath has been introduced as an alternative cleaning process, which is more environmentally friendly than traditional RCA cleaning.…”
Section: Introductionmentioning
confidence: 99%